THE EFFECT OF INFLUENT CONCENTRATION AND HYDRAULIC LOADING RATE (HLR) TO BOD AND COD REMOVAL ON ARTIFICIAL DOMESTIC WASTEWATER TREATMENT (GREY WATER) USING UASB REACTOR - Syafrudin Syafrudin; Sudarno Sudarno; Purwanto Purwanto; Iin Novitasari (Chemical Engineering Diponegoro University, 2014)
Upflow anaerobic sludge blanket (UASB) reactor is one of anaerobic biological treatment was develop in late 1970’s. UASB reactor is suitable for the tropic areas because it has a high temperature about 20°-30°C. Domestic wastewater is divided into two types, namely black water and grey water. But in this case used domestic grey water. Grey water is household wastewater from showers, sinks and kitchen. Grey water has a total 75% of the domestic wastewater volume. The research was conducted in laboratory scale. This study performed a variation of Hydraulic Loading Rate (HLR) and the influent concentration. There were 25 reactors include 5 variations of influent concentration and 5 Hydraulic Loading Rate’s (HLR) variation. The research could asses BOD5 and COD removal with treatment in UASB. Efficiency of BOD5 removal by varying the influent concentration and HLR was about 38%-75% and COD was about 40%-77%. The lower concentration could be increase efficiency BOD5 and COD removal. Influent concentration optimum occurred when middle concentration was about 840 mg/L COD and HLR optimum was 0,05 m3/m2/hour.